Pemantauan Kesehatan Jantung secara Klinis, Ekokardiografik dan Laboratoris pada Pasien Kanker Payudara yang Menjalani Kemoterapi Agen Antrasiklin: Penelitian Perintis Algoritme Kardioproteksi di RSUP Mohammad Hoesin Palembang - Puspita, Indah (The Indonesian Heart Association, 2025)
Objectives We analyzed echocardiography and laboratory results of breast cancer patients undergoing chemotherapy with anthracycline agents, to find cardiotoxicity risk and prevalence among South Sumatra population. Background Improved cancer therapy and early disease detection, increase the survival rate, also increase risk of CTRCD, range between 2 and 48% for patient with breast cancer treated by anthracyclines. There was limited data about prevalence of CTRCD in South Sumatra. Study of demographic factors and potential laboratory cardiac marker in specific population will give others additional important information. Methods In 2024, from March until November, 30 breast cancer patients were included in this analysis. Age 51,50 (41-69) years. All patients were in anthracycline chemotherapy treatment in Mohammad Hoesin General Hospital. Data of demography, laboratory and echocardiography was collected at baseline and after 3 cycles of treatment. Results Data collection and analysis was processed in outpatient department of Brain and Heart Installation Mohammad Hoesin General Hospital. From 30 patient, cardiovascular risk factors was detected: hypertension 30%, diabetes 10%, dyslipidemia 13,3%, body mass index 23,32 (13,30- 31,18), and almost all patients were not smoker (96,7%). Baseline to serial echocardiography showed that anthracycline did not affect the decrease of left ventricular ejection fraction (LVEF) (p=0,212), but correlated with the decrease of left ventricle global longitudinal strain (GLS) (p<0,05). There were 16 patients with >15% global longitudinal strain (GLS) reduction, without significant clinical heart failure signs and symptoms, known as mild asymptomatic cancer-therapy related cardiac dysfunction (CTRCD). Laboratory examination showed anthracycline agent was not correlated with Troponin T (p=0,093), NT-pro BNP (p=0,150), Serum Iron (p= 0,775), Total Iron Binding Capacity (TIBC) (p=0,692) and Transferrin Saturation (p=0,748). Ferritin level was affected by anthracycline agents (p= 0,026). Conclusion Higher prevalence of CTRCD in South Sumatra population was found. There was low incidence of cardiovascular risk factors in this population, indicated stronger isolated effect of chemotherapy agent for cardiac dysfunction progression. GLS by echocardiography measurement remain to be a good marker for cardiotoxicity related anthracycline agents. Ferritin level is potential parameter in guiding the stages and strategies in cancer treatment. Keywords: anthracycline, cardiac dysfunction, global longitudinal strain, ferritin